2012
DOI: 10.4161/cc.11.3.19008
|View full text |Cite
|
Sign up to set email alerts
|

TRIM8 modulates p53 activity to dictate cell cycle arrest

Abstract: A novel p53-inducible gene, PAG608, encodes a nuclear zinc finger protein whose overexpression promotes apoptosis interactions between p53 and these genes are generally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 36 publications
7
70
0
Order By: Relevance
“…TRIM8 interacts with and negatively regulates PIAS3, a protein inhibitor of IL-6-dependent activation of STAT3, a signaling pathway important for cancer development and progression [6]. In agreement with previously data, we recently reported TRIM8 as a new modulator of the p53-mediated tumor suppression mechanism [7]. Under stress conditions, such as UV exposure, we showed that p53 induces the expression of TRIM8, which in turn stabilizes p53 leading to cell cycle arrest and reduction of cell proliferation through enhancement of p21 and GADD45 expression [7].…”
Section: Introductionsupporting
confidence: 85%
“…TRIM8 interacts with and negatively regulates PIAS3, a protein inhibitor of IL-6-dependent activation of STAT3, a signaling pathway important for cancer development and progression [6]. In agreement with previously data, we recently reported TRIM8 as a new modulator of the p53-mediated tumor suppression mechanism [7]. Under stress conditions, such as UV exposure, we showed that p53 induces the expression of TRIM8, which in turn stabilizes p53 leading to cell cycle arrest and reduction of cell proliferation through enhancement of p21 and GADD45 expression [7].…”
Section: Introductionsupporting
confidence: 85%
“…Indeed, TRIM24 (Allton et al, 2009), TRIM39 (Zhang et al, 2012a,b) and TRIM59 (Zhou et al, 2014) help to degrade p53. In addition, TRIM8, TRIM13, TRIM19, TRIM21 and TRIM25 also affect p53 stability (Bernardi et al, 2004;Joo et al, 2011;Caratozzolo et al, 2012;Reddy et al, 2014;Zhang et al, 2015). TRIM28, TRIM29 and TRIM32 antagonize p53 function (Wang et al, 2005;Yuan et al, 2010;Liu et al, 2014).…”
Section: Role Of Trim-directed Precision Autophagy In Diseasementioning
confidence: 99%
“…9,10 Second, p53 binding partners, such as Hzf, Slug and hCAS, selectively regulate the expression of cell cycle arrest genes or apoptotic genes. [11][12][13][14] Third, some p53 targets, for example Glx2 (also called glyoxalase II) and Cdkn1a, regulate the survival of cells after DNA damage but do not affect the expression of other p53 targets. 15 Last, the levels of p53 in response to stresses also affect the outcome of various stresses.…”
Section: Rap2b a Novel P53 Target Regulates P53-mediated Pro-survivmentioning
confidence: 99%